Microcellular system design parameters for UNIMAS new campus - Hamdan, D. (University Malaysia Sarawak, UNIMAS., 2004)
This project will investigate the implementation of microcellular system design on UNIMAS new campus with assumption that there has not been any similar system applied to the campus. This project will try to determine the design parameters of the system and factors that involve in the design of the system base on the observation and information gathered during a few time visits to UNIMAS new campus.